Optimization of overcurrent relays coordination using Artificial Hummingbird Algorithm (AHA) - Noor Zaihah, Jamal; Arfan Haziq, Fathul Azmi (Institute of Electrical and Electronics Engineers Inc., 2023)
Overcurrent relay coordination is crucial for ensuring the reliable and selective operation of power system protection. This project investigates the application of the Artificial Hummingbird Algorithm (AHA) in optimizing overcurrent relay coordination to minimize operation time while meeting selectivity criteria and operating limits. The AHA is a bio-inspired metaheuristic algorithm that mimics the movement patterns of hummingbirds. The mathematical formulation of AHA involves position update equations and exploration-exploitation balance. The project focuses on implementing AHA in a simulated 8-bus and 9-bus power system network. The simulation results demonstrate the effectiveness of AHA in achieving optimal coordination among the overcurrent relays, improving coordination accuracy, and reducing operation time. AHA is compared with conventional methods and other metaheuristic algorithms, highlighting its advantages in terms of convergence speed and coordination accuracy. The findings provide valuable insights into the potential of AHA as an efficient and effective approach for overcurrent relay coordination. This project contributes to the field of power system protection by presenting a novel algorithmic solution for improving coordination and reliability in power system networks.